Research Trends in Group Investigation Learning Model for Critical Thinking Skills in Science Learning - Solikah, Anisa Ayu; Saputro, Sulistyo; Yamtinah, Sri; Masykuri, Mohammad (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
The 21st-century learning needs to be applied in science learning amidst the rapid development of this era to equip students with important skills, such as critical thinking skills. One of the factors that affect the success of learning is a learning model that has unique characteristics. The Group Investigation Learning Model is a learning model that allows students to play an active role in determining their learning goals and processes, including critical thinking skills. To see the application of the Group Investigation Learning Model in improving critical thinking skills, it is necessary to carry out a literature review study using the VOSviewer. This research used the publish or publish method with the Google Scholar database and obtained 985 articles selected using certain criteria to obtain 76 relevant articles. The results of the analysis with the VOSviewer based on network, overlay, and density visualization, show that the Group Investigation Learning Model is used to improve 21st-century skills, including critical thinking skills. Further analysis shows that research on high school biology subjects that apply the Group Investigation Learning Model dominates compared to other science fields. The implications of the results of this review can be a reference for further research to implement and develop learning models to improve critical thinking skills at the elementary and junior high school levels.